Behavioural challenges of minorities: Social identity and role models - Joseph Vecci; Tomas Zelinsky (PLoS ONE, 2019)
We present a lab-in-the-field experiment and surveys of marginalised Roma children in Slovakia to examine whether reminding Roma of their ethnicity reduces their performance in a cognitive task. Research on social identity and stereotypes has documented that when individuals feel that their social group is negatively stereotyped in a domain, their performance declines, which can reinforce discrimination. In an effort to break the cycle of negative stereotypes, we remind Roma subjects of either Roma or non-Roma role models. We find that the activation of a Roma's ethnicity reduces cognitive performance. In contrast, Roma exposed to Roma role models outperform those reminded of their ethnicity and of non-Roma role models. We then attempt to understand the channels through which social identity and role models affect performance. We show that priming the identity of a Roma has a direct effect on confidence, decreasing performance.
Keywords: D1; C93; J15; 330; Social Identity; artefactual field experiments; discrimination; role models; Roma